Penerapan Online Analytical Processing (OLAP) dalam Pengelolaan Data Karyawan - Aldisa, Rima Tamara (STMIK Budi Darma, 2022)
At this time many companies manage employee data manually from the process of recording employee data, employee absences which can result in data errors. Because of several things, it is necessary to have a system that can record every incoming data as well as a method that can control it so as not to experience excess or deficiency. The method used is the Online Analytical Processing (OLAP) method. The Online Analytical Processing (OLAP) method is an approach method to provide answers to requests for dimensional analysis processes quickly, the result to be achieved is to be able to design applications that are expected to provide convenience for companies to carry out the process of recording employee data, employee attendance to presentation. reports quickly, precisely and accurately